Public vehicle ETA system using machine learning - Kabir, Md. Miraz; Akil, Farhan Sadik; Mahmood, Ohinur Makamay (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.